2013
DOI: 10.1093/mnras/sts553
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear model of particle acceleration at colliding shock flows

Abstract: Powerful stellar winds and supernova explosions with intense energy release in the form of strong shock waves can convert a sizeable part of the kinetic energy release into energetic particles. The starforming regions are argued as a favorable site of energetic particle acceleration and could be efficient sources of nonthermal emission. We present here a non-linear time-dependent model of particle acceleration in the vicinity of two closely approaching fast magnetohydrodynamic (MHD) shocks. Such MHD flows are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 44 publications
(62 reference statements)
2
36
0
Order By: Relevance
“…Other possible PeV neutrino sources were proposed recently including semirelativistic hypernova remnants by Liu et al (2014) and shock acceleration of PeV CR particles in massive galaxy mergers or collisions by Kashiyama and Mészáros (2014). In the case of massive galaxy mergers/collisions CR acceleration in colliding shock flows modeled by Bykov et al (2013b) may play a role.…”
Section: Supernovae In Starburst Regionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other possible PeV neutrino sources were proposed recently including semirelativistic hypernova remnants by Liu et al (2014) and shock acceleration of PeV CR particles in massive galaxy mergers or collisions by Kashiyama and Mészáros (2014). In the case of massive galaxy mergers/collisions CR acceleration in colliding shock flows modeled by Bykov et al (2013b) may play a role.…”
Section: Supernovae In Starburst Regionsmentioning
confidence: 99%
“…On the other hand, they found that a model with proton acceleration in the cluster's supernova explosion(s) with subsequent interaction with the surrounding molecular material may explain both the GeV and TeV emission, but requires a very high energy input in protons and rather a slow diffusion. In §6.3 we shall discuss in some detail another potentially very fast and efficient mechanism of particle acceleration in colliding shock flows suggested by Bykov et al (2013b). The colliding shock flow occurs in a compact cluster where a strong expanding supernova shock is approaching a fast wind of a nearby massive star or collides with the supersonic wind produced by the compact cluster.…”
Section: Westerlund I Supercluster and The Magnetar Cxou J1647-45mentioning
confidence: 99%
See 3 more Smart Citations